EDUKASI STUNTING BAGI CALON PENGANTIN DALAM PERCEPATAN PENURUNAN STUNTING (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The prevalence of stunting in Indonesia based on SSGBI (Survey of Nutritional Status of Indonesian Toddlers) 2021 has been successfully reduced to 24.4 percent and in Province of South Sulawesi to 27.4 percent, but this prevalence is still higher than the tolerance value set by WHO. One of the stunting reduction efforts as stated in the National Action Plan for the Acceleration of Stunting Reduction (RAN PASTI) was the assistance of all prospective brides/prospective couples of childbearing age. The purpose of this study was to determine changes in knowledge of prospective brides through education about stunting in Marriage Guidance activities. This research was conducted at the Office of Religious Affairs (KUA) Biringkanaya District, Makassar City, integrated with Marriage Guidance activities. This research was conducted during March 2021. This research was an analytical study with a cross sectional approach. The sample in this study was all pairs of prospective brides who followed the Marriage Guidance as many as 76 pairs of prospective brides. The research was carried out by providing education through lectures and giving pocket books to prospective brides who attended Marriage Guidance. The measurement of knowledge variables before and after education was carried out through a questionnaire and analyzed using a computer. The results of the study showed that there was a change in knowledge before and after being given education to the prospective bride who followed marriage guidance. It is hoped that in the Marriage Guidance activity, stunting education is given to prospective brides as part of preparation before entering 1000 HPK.